Design of cost effective transistor by software simulation for profitable production. (24th January 2020) - Mukherjee, Debasis; Reddy, B.V. Ramana
Reduction of process cost is the key factor for profitability in any industry. Semiconductor industry is also not an exception of this rule. In this paper, a novel transistor structure has been proposed with reduced process cost and almost same functionality compared to conventional MOSFET transistor. Details fabrication steps of the novel transistor have been proposed. Working of the proposed structure resembles conventional MOSFET, but structure wise there are many differences. Necessity of source extension and drain extension has been uninvolved, resulting less fabrication cost and higher concentration of transistors in same chip area. Another improvement is removal of gate spacer, resulting cutting down of process cost. Both the conventional MOSFET and the proposed one have been simulated by Sentaurus TCAD toolkit for 7 nm technology generation. The performance of the proposed transistor has been found satisfactory compared to the conventional MOSFET as per the guidance given in International Technology Roadmap for Semiconductors or ITRS (2013) version.